Evaluation of Tebet Ecopark Management Based on Ecotourism Principles - Arum, Desilafia Sukma; Priyatmoko, Rakhman; Hamidah, Siti; Insani, Nailul (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2024)
Urban settings could have significant effects on how nature-based tourism develops. This study aimed to assess how ecotourism principles are currently put into practice at Tebet Eco Park (TEP), one of the urban parks in DKI Jakarta Province. It was also expected to recommend strategies for the maximum application of these principles to facilitate TEP to be a prominent urban ecotourism attraction. The research employed a qualitative descriptive methodology, involving data collection through field observations, interviews, and secondary data analysis. The research findings revealed that TEP has incorporated ecotourism principles, such as environmental conservation, local economic contributions, cultural preservation, education, and local community participation. However, the implementation of these principles has not been thoroughly optimized. Several indicators require refinement in their implementation, for example, the management should conduct scientific assessments related to TEP's carrying capacity which is crucial for environmental sustainability. Promoting TEP can lead to the establishment of a sustainable nature-based park in the urban landscape. This, in turn, can optimize the benefits for the local community and the entire population of Jakarta. Furthermore, the success of the implementation can also serve as a model for other nature-based urban parks in both Jakarta and other regions.